2021
DOI: 10.3390/ijerph181910023
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Omega-3 Fatty Acids of Wild and Farmed Mussels (Mytilus galloprovincialis) Consumed in Bulgaria: Human Health Risks

Abstract: The unique, closed ecosystem of the Black Sea is of significant global importance. The levels and health risk of some trace elements (As, Cd, Cr, Cu, Fe, Ni, Pb and Zn) in wild and farmed mussels (Mytilus galloprovincialis) collected from the Bulgarian part of the Black Sea were determined and using different approaches such as Estimated Daily Intake (EDI), Target Hazard Quotient (THQ), Hazard Index (HI), Target risk (TR), human health risk levels were assessed. The mean maximum concentrations of the elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…The raw M. galloprovincialis presented a favorable fatty acid composition with the predominance of PUFA (66.6%), followed by SFA (25.3%) and MUFA (8.1%). These data are in agreement with those reported previously for the same species from the Black Sea (Merdzhanova et al., 2019 ; Panayotova et al., 2021 ; Peycheva et al., 2021a , 2021b ; Stancheva et al., 2017 ; Stratev et al., 2017 ). However, other authors reported that SFA was the most abundant fatty acid group in raw M. galloprovincialis from the Mediterranean Sea (Biandolino et al., 2019 , 2021 ; Prato et al., 2019 , 2020 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The raw M. galloprovincialis presented a favorable fatty acid composition with the predominance of PUFA (66.6%), followed by SFA (25.3%) and MUFA (8.1%). These data are in agreement with those reported previously for the same species from the Black Sea (Merdzhanova et al., 2019 ; Panayotova et al., 2021 ; Peycheva et al., 2021a , 2021b ; Stancheva et al., 2017 ; Stratev et al., 2017 ). However, other authors reported that SFA was the most abundant fatty acid group in raw M. galloprovincialis from the Mediterranean Sea (Biandolino et al., 2019 , 2021 ; Prato et al., 2019 , 2020 ).…”
Section: Resultssupporting
confidence: 93%
“…The values below 1 (THQ < 1) reveal a lower level of exposure, which is associated with a daily exposure at this level is not likely to cause any harmful effects for human health during a lifetime in population (Bogdanović et al, 2014). According to our study, there were no THQ or HI values exceeding the value of 1 through the consumption of steamed M. galloprovincialis from Black Sea (Bulgaria) and it may be concluding that all tested elements in the steamed samples indicate that no health risk is present according to regulation or literature data (Jović & Stanković, 2014;Kalogeropoulos et al, 2012;Nekhoroshkov et al, 2021;Peycheva et al, 2021aPeycheva et al, , 2021b.…”
Section: Estimated Target Hazard Quotient Hazard Index and Target Can...mentioning
confidence: 53%
“…This method differs from our approach, in that the stepwise approach employed in the present study focuses on less time-and labor-consuming methods for unclassified samples. Many studies have reported that FAs provide considerable information regarding diet, trophic transfer, and specific metabolic pathways [32] and show potential for authenticating such information in food, such as dairy products, shellfish, and livestock [59][60][61]. However, the analysis of FAs in a large number of samples is time-consuming [59], whereas this study demonstrated that supplementary experiments for determining FA profiles with small sample sizes are quite effective because they can be selectively applied to necessary samples.…”
Section: Second Step I: Fa Composition For Geographical Authenticationmentioning
confidence: 77%
“…THQ is a ratio that illustrates the long-term non-carcinogenic exposure probabilities and reflects the risk associated with the consumption of the contaminated mussels [46]. The values below 1 (THQ < 1) are associated with lower levels of exposure, which is not likely to cause any harmful effects for human health during a lifetime in the population.…”
Section: Target Hazard Quotients and Total Hazard Indicesmentioning
confidence: 99%